Validation of the Latin American Spanish version of the face-name associative memory exam in a Colombian Sample. (1st December 2020) - Vila-Castelar, Clara; Papp, Kathryn V.; Amariglio, Rebecca E.; Torres, Valeria L.; Baena, Ana; Gomez, Diana; Rendon, Jorge; Samaroo, Aubryn; Lopera, Francisco; Rentz, Dorene M.; Quiroz, Yakeel T.
Abstract: Objective: The Face-Name Associative Memory Exam (FNAME) has been used to detect subtle cognitive changes in clinically normal older adults at increased risk for Alzheimer's disease. FNAME assesses learning and delayed recall for face-name pairs. The aim of this study is to introduce a Latin American Spanish version of the FNAME (LAS-FNAME), examine its psychometric properties, and provide preliminary normative data in a sample of clinically normal, Spanish-speaking individuals from Antioquia, Colombia. Method: 59 clinically-normal individuals (71% females) were recruited by the Grupo de Neurociencias in Antioquia (Colombia). Age ranged from 27 to 82 years ( M  = 50.31, SD  = 15.32) and years of education ranged from 2 to 17 years ( M  = 9.02, SD  = 4.11). All participants completed the LAS-FNAME and a brief neuropsychological evaluation. We examined associations between age, education, and sex and performance on the LAS-FNAME. Internal consistency, convergent and discriminant validity were also assessed. Test-restest reliability was computed for a subset of participants ( n  = 32). Results: LAS-FNAME exhibited moderate convergent validity with other memory measures (Free and Cued Selective Reminding Scale, r s =.465, p <.01; Wechsler Memory Scale III - Logical Memory Delayed Recall, r s =.479, p <.01). The subscales of the LAS-FNAME exhibited adequate internal consistency ( α =.825). Test-retest reliability analyses demonstrated consistency of scores over time. Normative data was stratified by age (<50, 50–65, >65) and low and high educational attainment (≤8 and >8 years of education, respectively). Conclusions: The LAS-FNAME is a valid and reliable measure to assess memory in clinically normal, Spanish-speaking individuals from Colombia for clinical and research purposes.